Potential benefits and descriptive norms in webrooming: an extended model of goal-directed behaviour. Issue 3 (3rd August 2021) - Arora, Sourabh; Sahney, Sangeeta; Pradhan, Debasis
Abstract : Purpose: This purpose of this paper is to extend the model of goal-directed behaviour by including the potential benefits of webrooming and descriptive norms to scrutinise the consumer's rationale and intent behind webrooming. Design/methodology/approach: A survey instrument was employed to collect the data. A total of 324 usable responses were obtained, and the structural equation modelling technique was used for analysis. Findings: The results of the study revealed that consumers utilised the information collected online to strike better deals offline. Also, webrooming not only stimulated smart shopper feelings amongst shoppers but also assisted them in avoiding certain risks associated with shopping online. Besides, support was also garnered for informative and possession benefits linked with webrooming. The findings demonstrated the positive impact of attitude, anticipated emotions and perceived behavioural control on desire, which in turn positively determined the intentions. Significant mediation impact was also observed between attitude and intentions via desire. However, past behaviour was evidenced to impact only intentions. Surprisingly, descriptive norms emerged as a stronger predictor of consumers' desire as opposed to subjective norms, which was found to be insignificant. Research limitations/implications: Information search and switching costs associated with webrooming have not been considered in this study. A larger sample size would help draw broader generalisations. Practical implications: While online retailers can utilise the findings of the study to convert webrooming shoppers into buyers, alternatively, offline stores can use the key insights to retain webroomers. Additionally, educators can use the findings of the study to teach the students about the changing retailing dynamics. Originality/value: The present study emerges as the first one to incorporate cognitive, affective and habitual factors collectively for a better understanding of the webrooming phenomenon.